Protein Markers Related to Non-halal Slaughtering Process of Rat as Mammal Animal’s Model Detected Using Mass Spectrometry Proteome Analysis - Alvina Nur Aini; Claude Mona Airin; Tri Joko Raharjo (Indonesian Journal of Chemistry, 2022)
Meat produced from non-halal slaughter is forbidden for Moslems. The slaughter methods contribute to the physiological response of animals expressed as different proteome profile. Proteome of two meat obtained from the halal and non-halal slaughter of Wistar rats (Rattus norvegicus) as an animal model was used to search for protein markers related to the slaughter method. The analysis employed Sodium Dodecyl Sulhate Polyacrylamide Gel Electrophoresis (SDS-PAGE), and High-Resolution Mass Spectrometer (HRMS) assisted with Label-Free Quantification (LFQ) Proteome Discoverer software. The non-halal slaughter contributed to the changes in protein expression in animal meat where thirteen proteins were up-regulated and three proteins were specifically identified in the non-halal slaughter, these three proteins are NSFL1 cofactor p47, transketolase, and Von Willebrand. There are three stable peptides identified of those three proteins, SYQDPSNAQFLESIR (m/z = 1755, z = +1) part of NSFL1 cofactor p47, LGQSDPAPLQHQVDVYQK (m/z = 2023, z = +1) part of transketolase, VPLLCTNGSVVHHEVINAMQCR (m/z = 2550, z = +1) part of Von Willebrand. Two of peptides can be targeted as markers in MRM mode LC-MS/MS routine analysis to authentication-halal slaughtering meat. The proposed MRM pair ions are 1755 to 1376, 1262, 1164, and 963, 2033 to 1355, 1016, and 762.